Euro zone crisis and EU governance: Tackling a flawed design and inadequate policy arrangements - Daniel Daianu (Center for Social and Economic Research (CASE), 2012)
This paper focuses on roots of strain in the European Monetary Union (EMU). It argues that there is need for a thorough reform of the governance structure of the Union in conjunction with radical changes in the regulation and supervision of financial markets. Financial intermediation has gone astray in recent decades and entailed a big bubble in the industrialized world. Waves of financial deregulation have enhanced systemic risks, via speculative behavior and growing inter-connectedness. Moreover, the EMU was sub-optimal from its debut and competitiveness gaps did not diminish against the backdrop of its inadequate policy and institutional design. The euro zone crisis is not related to fiscal negligence only; over-borrowing by the private sector and poor lending by banks, as well as a one-sided monetary policy, also explain this debacle. The EMU needs to complement its common monetary policy with solid fiscal/budget underpinnings. Fiscal rules and sanctions are necessary, but not sufficient. A common treasury (a federal budget) is needed in order to help the EMU absorb shocks and forestall confidence crises. A joint system of regulation and supervision of financial markets should operate. Emergency measures have to be comprehensive and acknowledge the necessity of a lender of last resort; they have to combat vicious circles. Structural reforms and EMU level policies are needed to enhance competitiveness in various countries and foster convergence. The EU has to work closely with the US and other G20 members in order to achieve a less unstable global financial system.
Keywords: F15; F36; F41; G21; H60; 330; Integration; Financial crisis; EMU; Sovereign debt; Governance reform; Eurozone; Öffentliche Schulden; Finanzkrise; Finanzmarktregulierung; Verwaltungsreform; Wirtschaftspolitik; EU-Politik; Eurozone; EU-Staaten